1987
DOI: 10.1016/s0735-1097(87)80477-1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic implantable cardioverter-defibrillator: Patient survival, battery longevity and shock delivery analysis

Abstract: The automatic implantable cardioverter-defibrillator (AICD) has been shown to reduce the mortality rate of patients with malignant ventricular tachyarrhythmias. This report describes experience with implantation of 36 automatic implantable cardioverter-defibrillators (AID-B and AID-BR models) in 22 persons over a 44 month patient follow-up period (mean 19.6 months). There were five deaths: two patients died suddenly 22 and 29 months, respectively, after their second implant, one died of congestive heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11]16,[20][21][22][23][24][25][26][27][28][29][30] The effectiveness of the ICD, as compared with control therapy, in reducing the hazard ratio for death varied among the trials in relation to their annual rate of death from any cause (correlation coefficient, ¡0.76) (Fig. [4][5][6][7][8][9][10][11]16,[20][21][22][23][24][25][26][27][28][29][30] The effectiveness of the ICD, as compared with control therapy, in reducing the hazard ratio for death varied among the trials in relation to their annual rate of death from any cause (correlation coefficient, ¡0.76) (Fig.…”
Section: Efficacy Of the Icdmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11]16,[20][21][22][23][24][25][26][27][28][29][30] The effectiveness of the ICD, as compared with control therapy, in reducing the hazard ratio for death varied among the trials in relation to their annual rate of death from any cause (correlation coefficient, ¡0.76) (Fig. [4][5][6][7][8][9][10][11]16,[20][21][22][23][24][25][26][27][28][29][30] The effectiveness of the ICD, as compared with control therapy, in reducing the hazard ratio for death varied among the trials in relation to their annual rate of death from any cause (correlation coefficient, ¡0.76) (Fig.…”
Section: Efficacy Of the Icdmentioning
confidence: 99%
“…Multiple studies have shown that implantable cardioverter defibrillators (ICDs) reduce sudden cardiac death in high risk patients who present with sustained ventricular arrhythmias, 1–20 and the majority of these patients will receive the first defibrillator shock within the first 6 to 7 months following implantation 6 , 16 , 21,22 . Most patients presenting with sustained ventricular arrhythmias will eventually receive appropriate defibrillator shock therapy, with the cumulative incidence of appropriate therapy of 13%‐47% after 1 year, and 63%‐80% after 4 to 5 years in high risk patients 7 , 13 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The probability density function can sometimes be satisfied by SVT with wide QRS complexes or, conversely, may be insensitive to relatively narrow or "spikey" VT. As a result, the device can discharge during tachycardias other than VT. As mentioned previously, nonsustained ventricular tachyarrhythmias can also trigger device discharge due to the "committed" nature of the current AICD. Due to these problems, questionably appropriate or spurious device discharges occur commonly with an incidence of 8-41% in different series.64656773, 75 The lack of telemetry in the current generation of the AICD makes determination of the appropriateness of a discharge in a conscious patient very difficult. Interactions with antibradycardia pacemakers have largely arisen from sensing difficulties.76 Unipolar pacemaker spikes as well as paced complexes can be sensed by the AICD, leading to double counting and satisfaction of rate criteria for device discharge.…”
Section: Physiology Of Cardioversion and Defibrillationmentioning
confidence: 99%